Work Life Imbalance and Psychosocial Tribulations among Working Women - Chaudhary, R R Rajan; Bagga, Rajesh (International Journal of Management Excellence (ISSN: 2292-1648), 2018)
With the changing scenario, there is vast increase in the number of working women.Women are competent enough to contribute for the betterment of any of the organisation. They are sharp, intelligent, empathetic, flexible and with energy to work hard for the both fronts i. e. office as well the home. They are with dual responsibility to manage multiple tasks at home and at the work. The increasing expectations at both ends make the situation difficult for women , as a result they face difficulty in maintaining a required balance between work and life. This lack of balance results in further problems for working women. Because of work overload, career aspirations, competition, peer pressure at workplace and child care, elder care, relationship maintenance, other household responsibilities at home, it becomes very difficult for females to contribute to the maximum at both ends. And because of this imbalance, females remain with some guilt and stress, as a result came across with many psychosocial tribulations, that may affect their performance as well as health also. This paper examined the concept of work life balance and how women juggle for multiple tasks and as a result face work life imbalance. And paper also revealed that working women with dual roles suffer from psychosocial problems and different strategies have also been discussed which can be of help to working women in maintaining a balance between work and life.